Prevalence and related factors of depressive symptoms among HIV/AIDS in Ningbo, China: A cross-sectional study - Chen, Suting; Hong, Hang; Xu, Guozhang (Frontiers in Psychiatry, 2022)
Background Depressive symptoms were common among HIV/AIDS patients. Previous studies had shown that HIV-infected patients were twice as likely to be diagnosed with depression as the general population. However, only few studies have explored the prevalence and related factors of depressive symptoms among HIV/AIDS in China. Materials and methods A cross-sectional study was conducted to study the prevalence of depressive symptoms among HIV/AIDS from January to December 2021 through the database of HIV/AIDS antiretroviral therapy and psychological evaluation system in Ningbo, China. The Patient Health Questionnaire-2 (PHQ-2) was used to screen for depressive symptoms (PHQ-2 > 0), the Patient Health Questionnaire-9 (PHQ-9) was used to diagnose depressive symptoms, and multivariate Logistic regression model was carried on to evaluate the related factors. Results A total of 3,939 HIV/AIDS patients were enrolled, and the age of initiation of antiretroviral therapy was 37.15 (IQR = 28.41–48.73) years. Among them, 3,230 (82.00%) were male, 3,844 (97.59%) were Han nationality, 1,391 (35.49%) were unmarried, 1,665 (42.27%) were homosexual transmission, and 2,194 (55.70%) were HIV-infected patients. There were 265 patients (6.73%) with depressive symptoms, and the proportion of mild, moderate, moderate and severe depressive symptoms was 4.01% (158/3939), 1.65% (65/3939), 0.76% (30/3939), and 0.30% (12/3939), respectively. Multivariate analysis showed that married [odds ratio (OR) = 0.675, 95% CI = 0.501–0.908], divorced or widowed (OR = 0.571, 95% CI = 0.380–0.860), homosexual transmission (OR = 1.793, 95% CI = 1.349–2.396) were associated with depressive symptoms among HIV/AIDS. Conclusion The prevalence of depressive symptoms among HIV/AIDS patients was 6.73% in Ningbo, China. More attention should be paid to the psychological status of unmarried and homosexual HIV/AIDS patients in Ningbo and timely psychological intervention or treatment should be given to those patients with depressive symptoms.